EFEKTIVITAS METODE AKTIVITAS ANTIOKSIDAN PADA FRAKSI KECAP MANIS DAN MODEL GLUKOSA-GLISIN-SISTEIN - Rosida, Dedin F; Wijaya, C. Hany; Apriyantono, Anton; FR, Zakaria (UPN VETERAN JAWA TIMUR, 2011)
The oxidative browning is considered to have a contribute to the flavor, antioxidative activity and color of food. As a result of this Maillard reaction, a variety of by products, intermediates and brown pigmens (melanoidins) are produced. The objectives of this research was to study the effect of antioxidant activity method determination on model and soysauce. The soy sauce were prepared from sucrose or coconut sugar and moromi. The soysauce and model were fractionated by ultrafiltration in a molecular weight ranging between 10 kDa to 100 kDa. In this study, we report that fractions of soysauce. and model have the ability to scavenging more strongly DPPH radical on the fraction with molecular weight of 30 kDa than 100 kDa, whereas the inhibition of oil oxidation was stronger in the fraction with molecular weight <10 kDa to 30 kDa and its activity is more greater than BHT 200 ppm, although the effect of antioxidants in soy sauce is greater than the model. Each fraction of soy sauce and a model had a specific effect on the inhibition method of oil oxidation or sscavenging of free radicals